Rationally designed hierarchical TiO2@Fe2O3 hollow nanostructures for improved lithium ion storage - Luo, Jingshan (2014)
Hollow and hierarchical nanostructures have received wide attention in new-generation, high-performance, lithium ion battery (LIB) applications. Both TiO2 and Fe2O3 are under current investigation because of their high structural stability (TiO2) and high capacity (Fe2O3), and their low cost. Here, we demonstrate a simple strategy for the fabrication of hierarchical hollow TiO2@Fe2O3 nanostructures for the application as LIB anodes. Using atomic layer deposition (ALD) and sacrificial template-assisted hydrolysis, the resulting nanostructure combines a large surface area with a hollow interior and robust structure. As a result, such rationally designed LIB anodes exhibit a high reversible capacity (initial value 840 mAh g−1), improved cycle stability (530 mAh g−1 after 200 cycles at the current density of 200 mA g−1), as well as outstanding rate capability. This ALD-assisted fabrication strategy can be extended to other hierarchical hollow metal oxide nanostructures for favorable applications in electrochemical and optoelectronic devices.